A Class of Optimal Portfolio Liquidation Problems with a Linear Decreasing Impact. (26th April 2017) - Ma, Jiangming; Yin, Zheng; Chen, Hongjing
Abstract : A problem of an optimal liquidation is investigated by using the Almgren-Chriss market impact model on the background that the n agents liquidate assets completely. The impact of market is divided into three components: unaffected price process, permanent impact, and temporary impact. The key element is that the variable temporary market impact is analyzed. When the temporary market impact is decreasing linearly, the optimal problem is described by a Nash equilibrium in finite time horizon. The stochastic component of the price process is eliminated from the mean-variance. Mathematically, the Nash equilibrium is considered as the second-order linear differential equation with variable coefficients. We prove the existence and uniqueness of solutions for the differential equation with two boundaries and find the closed-form solutions in special situations. The numerical examples and properties of the solution are given. The corresponding finance phenomenon is interpreted.